Hygiene Personal pada Penjual Nasi Kucing - Erfianto, Rudi; Koesyanto, Herry (HIGEIA (Journal of Public Health Research and Development), 2017)
Pangan sebagai salah satu kebutuhan primer manusia harus diperhatikan aspek gizi dan kesehatannya. Salah satu pertimbangan konsumen dalam meemilih makanan adalah faktor keamanan makanan. Makanan yang aman yaitu telah memenuhi syarat sanitasi dan higiene personal. Tujuan penelitian ini adalah mengetahui hubungan antara tingkat pendidikan dengan hygiene personal, dan hubungan antara tingkat pengetahuan dengan hygiene personal. Jenis penelitian ini adalah explanatory research dengan pendekatan cross sectional. Populasi sebanyak 72 responden dan sampel berjumlah 62 responden. Instrumen yang digunakan yaitu kuesioner dan observasi. Hasil penelitian yaitu (1) tidak adanya penjual yang mencuci tangan sebelum menyajikan, (2) Penjual yang mencuci peralatan dengan sabun dan air mengalir sebesar 10%, (3) Penjual yang menyediakan tempat sampah sebesar 70% (4) Penjual yang merokok sebesar 60%. Kesimpulan penelitian ini adalah ada hubungan antara tingkat pendidikan dengan praktik hygiene personal (p value= 0,032), ada hubungan antara tingkat pengetahuan dengan praktik higiene personal (p value=0,010). Kata Kunci: pendidikan,pengetahuan dan higiene personal. Food is one of the primary needs of man must be considered nutritional and health aspects. Food safety is one of consideration is used by selector food. Saved food is food that has require of health sanitation and personal hygiene. The purpose of this study is to investigate the relationship between level of education and personal hygiene, and relationship between the levels of knowledge with personal hygiene. The research method is explanatory research with cross sectional design. The number of population and samples respectively is 72 and 62 respondents. The questionnaires and observation is used for instrument. The result is ( 1 ) the absence of sellers who wash their hands before serving , ( 2 ) Sellers who wash equipment with soap and water flow by 10 % and 90 % which are not , ( 3 ) Seller providing bins for 70 % and 30 % which does not provide , ( 4 ) Sellers who smoke by 60 % and non smokers by 40 % . This is certainly an issue that needs to know the causes and risk factors for customers of students as consumers. Conclusion of this research is that there is a relationship between level of education and personal hygiene practices ( p value = 0.032) , there is a correlation between the level of knowledge in the practice of personal hygiene ( p value = 0.010). Keyword: education , knowledge and personal hygiene